Thermodynamic Indicator Of Exergy In Measuring Of Research Performance: A Review Article - Nadia Sanee; Seyed Javad Ghazi Mirsaeid (Tehran University of Medical Sciences, 2015)
Background and Aim: Thermodynamic indicators are considered in scientometrics studies to survey research performance as the Exergy that is most important ones. Therefore, this article is aimed to introduce, review, definition, application and importance of Exergy. Materials and Methods: This study is a review article that determined by using related literatures with thermodynamic indicators of scientometrics by library research, and simple and advanced searches of English papers on valid websites. 30 English papers were retrieved and 24 articles related to this study were selected but among Persian literatures, no related papers were found. Results: Exergy is a thermodynamic measure which reperesenting a maximum useful work that a system can perform in order to create balance. This indicator is applicable in bibliometrics and as an indicator of research performance for ranking of research institutions. Conclusion: According to the role of exergy in assessing the research performance of individuals and organizations, and its advantage over H-index, due to consideration of all the articles and all the citations, this indicator can offer new reperesentation of rankings.